THE INFLUENCE OF “CRUELLA” MOVIE TO IMPROVE STUDENTS’ VOCABULARY, A CASE OF XI GRADE STUDENTS’ MAN 1 BREBES IN THE ACADEMIC YEAR 2022/2023 - Annisa Salmawati (Penerbit Lafadz Jaya, 2022)
This study was based on the fact that there are still many students who have not mastered the vocabulary correctly, and only a few students have mastered the vocabulary. The study aims to determine how much the